Space and Nuclear Weaponry in the 1990's
XV, 205 p.
Keywords: A collection of papers that were the result of meetings held in Italy under the auspices of the International School on Disarmament and Research on Conflicts (ISODAROC). The primary aim of the meetings was to explore the prospects for space and nuclear weaponry in the coming decade.